2021
DOI: 10.3390/ani11113204
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Oxidative Profiles in Plasma and Saliva in Dairy Cows during Pregnancy

Abstract: Increased metabolism that occurs during pregnancy can result in oxidative stress which is harmful to cells and, consequently, for the proper functioning of the whole organism. Plasma and recently also saliva are important resources for evaluating physiological and pathological conditions in animals. The study aimed to investigate the influence of the metabolic state on the effectiveness of the antioxidant profile of plasma and saliva during the pregnancy of cows. Seventy-six healthy pregnant and twelve non-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…To assess the extent of damage to cell membranes, we used an indirect method, involving the monitoring of a persistent radical cation formed in the reaction of alkoxy and peroxy radicals derived from hydroperoxides with a suitable additive such as DEPPD [67]. The analysis of the results indicated that at 12 h post-hatch, lipid peroxidation is increased in the serum and heart of birds receiving Zn-Gly chelate in ovo and in the pectoral muscle of birds receiving the multi-strain probiotic and Zn-Gly (group III) or Zn-Gly (group IV).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the extent of damage to cell membranes, we used an indirect method, involving the monitoring of a persistent radical cation formed in the reaction of alkoxy and peroxy radicals derived from hydroperoxides with a suitable additive such as DEPPD [67]. The analysis of the results indicated that at 12 h post-hatch, lipid peroxidation is increased in the serum and heart of birds receiving Zn-Gly chelate in ovo and in the pectoral muscle of birds receiving the multi-strain probiotic and Zn-Gly (group III) or Zn-Gly (group IV).…”
Section: Discussionmentioning
confidence: 99%
“…As a component of the ungulate strategy for winter season adaptation, body fat reserves are used in addition to food, which could also affect ROS formation, leading to oxidative stress and lipid peroxidation ( 1 , 8 ). In our study we found lower values of plasma MDA in the third trimester, which could be an indirect result of CAT activity and the elevation of total glutathione and GSSG pools, suggesting an effective antioxidant system compensation ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic changes in the body involve the production of ROS, the ROS balance being controlled by the enzymatic and non-enzymatic antioxidant systems. The superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR) and paraoxonase 1 (PON1) enzymes diminish the excess of ROS, and are supported by the non-enzymatic components glutathione, bilirubin and uric acid in stabilisation of the redox state ( 8 ). Also, plasma proteins such as albumins prevent the production of free radicals by binding free metals ( 27 ).…”
Section: Introductionmentioning
confidence: 99%